Microstructure dependence of fatigue crack propagation behavior in wrought magnesium alloy - S. Morita; S. Fujiwara; T. Hori; N. Hattori; H. Somekawa; T. Mayama (Fracture and Structural Integrity)
This paper deals with the fatigue crack propagation behavior of rolled AZ31B magnesium alloy (grain size: approximately 40 m). Fatigue crack propagation tests were performed on single edge notched tension specimens at a stress ratio of R = 0.1 and a frequency of 10 Hz at room temperature. Loading axes were parallel to the rolling direction; fatigue cracks propagated parallel to the transverse direction (L-T specimen), parallel to the short transverse direction (L-S specimen). Loading axis was perpendicular to the rolling direction; fatigue cracks propagated parallel to the transverse direction (S-T specimen). The crack growth rate (da/dN) of the L-S specimen was several times lower than that of the L-T specimen in the examined stress intensity factor range (K). Fracture surfaces of the L-T and L-S specimens showed many steps parallel and perpendicular, respectively, to the macroscopic crack growth direction. The da/dN of the S-T specimen was higher than that of the L-T and L-S specimens in the examined K. The fracture surface was covered by quasi-cleavage facets independent of macroscopic crack growth direction, and the fracture surface roughness at low K was larger than that at high K.